2020
DOI: 10.1186/s12875-020-01309-4
|View full text |Cite
|
Sign up to set email alerts
|

The global prevalence of turnover intention among general practitioners: a systematic review and meta-analysis

Abstract: Background General practitioners (GPs) are the foundation of any primary healthcare system. Their quality and quantity are directly associated with the effectiveness and quality of the health services of a nation. GPs’ shortage and turnover have become an important issue in developed and developing countries. An accurate estimate of turnover intention prevalence among GPs would have important health policy implications, but the overall prevalence is unknown. We aimed to summariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
5
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 55 publications
1
54
5
6
Order By: Relevance
“…We found that nearly half (49.75%) of emergency physicians had turnover intention. Compared to previous studies of psychiatrists (20%) [ 23 ], general practitioners (47%) [ 24 ], and emergency department nurses (23%) [ 25 ], emergency physicians showed higher levels of turnover intention, which indicated that fully attention should be paid to this community. In addition, we identified a number of representative factors that clearly correlate with the increasing of turnover intention among emergency physicians, which could provide references for targeted measures.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…We found that nearly half (49.75%) of emergency physicians had turnover intention. Compared to previous studies of psychiatrists (20%) [ 23 ], general practitioners (47%) [ 24 ], and emergency department nurses (23%) [ 25 ], emergency physicians showed higher levels of turnover intention, which indicated that fully attention should be paid to this community. In addition, we identified a number of representative factors that clearly correlate with the increasing of turnover intention among emergency physicians, which could provide references for targeted measures.…”
Section: Discussioncontrasting
confidence: 67%
“…However, it has not been reported whether emergency physicians have higher turnover intentions. Previous studies on turnover intention mostly focused on psychiatrists [ 23 ], general practitioners [ 24 ], emergency department nurses [ 25 ] and other groups. Therefore, the purpose of this study was to explore the prevalence of turnover intentions (including switching departments and turnover) of emergency physicians and influencing factors, which could provide a reference for global health-care policy makers and researchers to solve the shortage of physicians.…”
Section: Introductionmentioning
confidence: 99%
“…This difference was possibly related to social environment, the level of economic development and the working environment among various countries. Also, due to the heavy workloads and working without adequate rest that the rate of the turnover intention among physicians in emergency department was much higher than that of radiologists (33.3%), general practitioners (47%) and physicians in intensive care (26%) [ 24 - 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent data have shown that the GP workforce in England is going through a major crisis, 1 reflected in increasing rates of early retirement and intentions to reduce hours of working or leave their practice in the near future. 2 Despite this being a common problem for other European countries 3 and globally, 4 it seems to be particularly serious for the UK. 3 5 According to an international survey of GPs from 2015, approximately 30% of GPs want to leave their profession within 5 years.…”
Section: Introductionmentioning
confidence: 99%
“…Low retention or decreasing retention levels over time and high turnover rates are major issues for NHS primary care. High GP turnover is a concern for several reasons: it may be associated with practices experiencing recurring problems with recruitment and retention 10 ; it may affect the ability to deliver primary care services 4 and undermine continuity of care which in turn may affect the quality of patient care. For instance, healthcare received from multiple GPs can lead to conflicting therapeutic treatments and fragmented care.…”
Section: Introductionmentioning
confidence: 99%